Comparative Evolutionary Patterns of Burkholderia cenocepacia and B. multivorans During Chronic Co-infection of a Cystic Fibrosis Patient Lung - Hassan, A. Amir; dos Santos, Sandra C.; Cooper, Vaughn S.; Sá-Correia, Isabel (Frontiers in Microbiology, 2020)
During chronic respiratory infections of cystic fibrosis (CF) patients, bacteria adaptively evolve in response to the nutritional and immune environment as well as influence other infecting microbes. The present study was designed to gain insights into the genetic mechanisms underlying adaptation and diversification by the two most prevalent pathogenic species of the Burkholderia cepacia complex (Bcc), B. cenocepacia and B. multivorans. Herein, we study the evolution of both of these species during coinfection of a CF patient for 4.4 years using genome sequences of 9 B. multivorans and 11 B. cenocepacia. This co-infection spanned at least 3 years following initial infection by B. multivorans and ultimately ended in the patient’s death by cepacia syndrome. Both species acquired several mutations with accumulation rates of 2.08 (B. cenocepacia) and 2.27 (B. multivorans) SNPs/year. Many of the mutated genes are associated with oxidative stress response, transition metal metabolism, defense mechanisms against antibiotics, and other metabolic alterations consistent with the idea that positive selection might be driven by the action of the host immune system, antibiotic therapy and low oxygen and iron concentrations. Two orthologous genes shared by B. cenocepacia and B. multivorans were found to be under strong selection and accumulated mutations associated with lineage diversification. One gene encodes a nucleotide sugar dehydratase involved in lipopolysaccharide O-antigen (OAg) biosynthesis (wbiI). The other gene encodes a putative two-component regulatory sensor kinase protein required to sense and adapt to oxidative- and heavy metal- inducing stresses. This study contributes to understanding of shared and species-specific evolutionary patterns of B. cenocepacia and B. multivorans evolving in the same CF lung environment.